The many faces of allergy: what are we doing wrong? - article Editorial (Медицинский совет, 2018)
The prevalence of allergic diseases has increased worldwide over the past decades. Despite significant progress in understanding the causes and mechanisms of allergic inflammation, and the development of approaches to the treatment of allergic diseases, the real practice of providing medical care to patients with allergic diseases remains far from perfect. The problem was addressed at the symposium «The Many Faces of Allergy: What are We Doing Wrong?» held within the framework of the AllRussian Conference «Clinical Immunology and Allergology to Practical Health Care».